Sadchikov Pavel E. Features of Molecular Sensitisation Profile in Infants with Risk of Allergic Diseases - Irina A. Belyayeva; Tatyana V. Turti; Leyla S. Namazova-Baranova; Elena P. Bombardirova; Elena A. Vishneva; Elena V. Kaytukova; Kamilla E. Efendieva; R. A. Shukenbaeva; Pavel E. Sadchikov (Вопросы современной педиатрии, 2023)
Background. For now, there is little data on sensitivity features to specific allergen antigens in infants with initial allergy manifestations.Objective. The aim of the study is to determine the features of the primary molecular sensitisation profile in infants with risk of atopic disease according to their postnatal age.Methods. Full-term infants with burdened familial allergic history and/or skin/gastrointestinal allergy symptoms were examined: Group 1 — 50 children, age — 2.0 [1.0–3.0] months; Group 2 — 35 children, age — 9.0 [8.0–11.0] months.Results. The hereditary atopy risk was observed in 74% of cases (37/50) in Group 1 and in 71% of cases (25/35) in Group 2. 38% of children (19/50) in Group 1 were breastfed, in Group 2 — 60% of children (21/35). Supplemental feeding was implemented in 5.5 [5.0–6.0] months. Sensitisation was reported in 10% and 37% of children. Children of Group 1 were sensitised to food allergen antigens: cow's milk/meat (Bos d 6, Bos d 8), egg-white (Gal d 1, Gal d 2, Gal d 3), soybeans (Gly m 6), shrimps (Pen m 4); airborne allergens: house dust mite (Blo t 5, Der h 10), Anisakidae (Ani s 3), cockroach (Bla g 7). Children of Group 2 were sensitised to food allergen antigens: cow's milk (Bos d 6), egg-white (Gal d 1, Gal d 2), soybeans (Gly m 6), peanut (Ara h 1, Ara h 2, Ara h 6), kiwi (Act d 1), corn (Tri a 19); airborne allergens: cat (Fel d 1, Fel d 4), birch pollen (Bet v 1). Polyvalent sensitisation was revealed in 4% and 6% of cases, respectively.Conclusion. Infants have much wider range of allergens to which they are sensitive than it is commonly believed. Beside obligate food allergens, sensitisation can be caused by airborne allergens: house dust mites, epidermal, birch pollen; crossreactive component — tropomyosin.